2006
DOI: 10.1309/bvcbnkyh7c1um71y
|View full text |Cite
|
Sign up to set email alerts
|

Iron Binding Saturation and Genotypic Testing for Hereditary Hemochromatosis in Patients With Liver Disease

Abstract: We compared the results of HFE genotype with tests for iron binding saturation (IBS) in 190 consecutive patients with liver disease using 2 IBS cutoff levels: 45% and 60%. Saturation was more than 45% in 117 patients (61.6%) and more than 60% in 89 (46.8%). The number of patients (10) with the highest-risk HFE genotype (C282Y homozygote) was higher than expected. Elevated IBS cannot be used to predict genotype. There was a modest association of C282Y homozygosity with increased IBS (7 of 10, saturation >45% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(17 reference statements)
0
2
0
1
Order By: Relevance
“…There are a limited number of studies reporting C282Y-homozygosity in unselected patients with liver disease [98][99][100]. Three to 5.3% of patients were C282Y-homozygous, which is about 10-fold higher than the reported prevalence in the general population.…”
Section: Liver Diseasementioning
confidence: 83%
“…There are a limited number of studies reporting C282Y-homozygosity in unselected patients with liver disease [98][99][100]. Three to 5.3% of patients were C282Y-homozygous, which is about 10-fold higher than the reported prevalence in the general population.…”
Section: Liver Diseasementioning
confidence: 83%
“…Moreover, iron overload was more intense in the presence of liver disease, as shown by higher serum concentrations of ferritin and transferrin saturation. Although ferritin and transferrin saturation may be questioned as markers of iron overload in the presence of liver disease, since ferritin elevation may result from necroinflammatory activity, and decreased hepatic protein production may occur secondary to liver disease [36] , resulting in lower TIBC and higher transferrin saturation, previous studies in patients with liver disease have shown significantly higher ferritin levels in patients with alcohol-related liver disease [12] . Furthermore, in the present study, we observed a positive correlation between serum ferritin and the degree of hepatic iron deposition in patients who had a liver biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Portadores de cirrose hepática apresentam maiores graus de sobrecarga de ferro. 91,99 No presente estudo, observou-se que a média dos índices séricos de ferritina foi de 1873,6 ng/mL e ST de 78,82% e no grupo de portadores de HH-HFE, a média de ferritina sérica foi de 2676,75 ng/mL e ST 91,02%. Em se tratando de casuística com 64,8% de portadores de cirrose hepática e elevada frequência de fatores de risco para sobrecarga de ferro, tais resultados correspondem ao esperado.…”
Section: Análise Dos Marcadores Séricos De Sobrecarga De Ferrounclassified